Dynamics and mechanisms of photoinduced electron transfer and related phenomena : proceedings of the Yamada Conference XXIX on Dynamics and Mechanisms of Photoinduced Electron Transfer and Related Phenomena, Senri, Osaka, Japan, May 12-16, 1991 - Mataga, Noboru, 1927-2011; Okada, Tadashi, 1939-; Masuhara, Hiroshi, 1944- (North-Holland delta series., 1992)
This book contains papers which examine fundamental aspects of photoinduced electron transfer reactions, an area in which a number of breakthroughs have recently occurred. The book is divided into four parts. Parts I and II are mainly concerned with the fundamental aspects of the inter- and intra-molecular charge transfer, electron transfer and related phenomena such as solvent effects, solvation dynamics, energy gap dependences and radical pair dynamics. Part III is concerned with electron transfer and energy transfer phenomena in polymers, films, crystals, and other confined systems. In Part IV, the mechanisms of the energy and electron transfer in biological photosynthetic systems, proteins and reaction center systems are discussed.